Updated Equivalent Axial Load Method for Design of Steel Beam-Columns - Reynolds, Mathew; Uang, Chia-Ming (Engineering Journal, 2019)
The equivalent axial load method is a design aid that aims to select candidate wide-flange beam?columns with minimal iteration. The method itself was described in previous editions of the AISC Steel Construction Manual, but has been removed in recent editions. An expanded version of the tables for sizing of both shallow and deep beam-columns based on the latest edition the AISC Manual is presented. Several examples of uniaxial and biaxially loaded beam-columns are provided to demonstrate the effectiveness of the method. The method is validated using a programmed heuristic which designed beam-columns from randomly generated scenarios.